The Validity of Multi Contracts on SBSN (Sukuk) Ijarah Sale and Lease Back in the MUI DSN Fatwa - Panji Adam Agus Putra; Redi Hadiyanto; Indra Wijaya; Dina Rahmania (LAA MAISYIR: Jurnal Ekonomi Islam, 2020)
The National Sharia Council-Indonesian Ulema Council has issued a fatwa regarding sukuk, namely Fatwa Number 72 of 2008 concerning SBSN Ijarah Sale and Lease Back. The concept of sukuk in the DSN-MUI Fatwa uses the concept of hyrid contracts. This has resulted in differences of opinion from experts regarding the legal status of the DSN fatwa using the multi-agreement in the SBSN Ijarah Sale and Lease Back. The research method used is normative juridical. While the type of this research is descriptive analysis and the data collection technique is literature study. The data analysis method is qualitative. The results showed that; first, takyif fiqh in the SBSN scheme uses the al-bai 'wa al-isti'jar contract, which is a combination of the bai' contract and the ijârah contract; second, the hybrid contract concept in the DSN-MUI Fatwa No. 72 regarding SBSN Ijarah Salse and Lease Back is a hybrid contract agreement that does not violate the rules and boundaries of the hybrid contract theory that have been formulated by the scholars.